2020
DOI: 10.7717/peerj.9388
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation in the skull morphology of the lesser grison (Galictis cuja: Carnivora, Mustelidae) from two Brazilian ecoregions

Abstract: Background The lesser grison (Galictis cuja) is one of the least known carnivores in the Neotropical region. Its wide geographical occurrence and range of habitats could lead to morphological variations along its distribution. So, this study aimed to investigate the variation in skull shape and size of this species, by testing the existence of ecotypes adapted to their respective environments (Uruguayan savanna and Atlantic Forest), as well as its relationship with selected abiotic variables. Methods The sku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
(91 reference statements)
1
4
0
2
Order By: Relevance
“…As observed in most Musteloidea [ 7 , 31 , 32 , 63 , 64 ], we found a significant Sexual Size Dimorphism (SSD) in otter skulls from Great Britain, with males larger than females. Differences in skull size are usually related to bite force [ 30 ].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…As observed in most Musteloidea [ 7 , 31 , 32 , 63 , 64 ], we found a significant Sexual Size Dimorphism (SSD) in otter skulls from Great Britain, with males larger than females. Differences in skull size are usually related to bite force [ 30 ].…”
Section: Discussionsupporting
confidence: 75%
“…This high feeding plasticity is expected to be reflected in the cranial and mandibular morphology with modifications expected, especially in the dentition and masticatory muscle attachment area, as observed for members of the order Carnivora [ 21 , 28 ]. Furthermore, differences in diet may also be reflected in sexual dimorphism of the skull with respect to size and shape [ 29 32 ], as specific adaptations can improve the fitness and reduce intraspecific resource competition [ 33 ]. Although mustelids are known usually to show sexual dimorphism only with respect to size, and not shape [ 7 , 29 31 ], advances in methodology may now permit more nuanced analyses.…”
Section: Introductionmentioning
confidence: 99%
“…As with traditional morphometrics studies, GMM studies on intraspecific variation in cranial shape in mustelids found significant differences in cranial size both between sexes and among populations. However, results for cranial shape are varied with significant differences in shape between sexes being reported in fishers (Pekania pennanti; Law, 2020) and two marten species (Martes martes, M. foina; Loy et al, 2004), but no such differences being found in Neotropical otters (Lontra longicaudis; Hernández-Romero et al, 2015), lesser grisons (Galictis cuja; Migliorini et al, 2020) or American martens (Martes americana; Law, 2020). Finally, some of these intraspecific studies also found significant differences in cranial shape among populations (Hernández-Romero et al, 2015;Loy et al, 2004), and between age classes (Law, 2020;Law et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…(Helgen & Schiaffini, 2016;Kasper et al, 2013). É amplamente distribuído na América do Sul, com registros no sul do Peru, oeste da Bolívia, centro do Chile, Uruguai, Paraguai, Argentina e Brasil (Migliorini et al, 2020;Yensen & Tarifa, 2003). É encontrado em uma grande variedade de hábitats, desde vegetações costeiras, matagais áridos e florestas úmidas (Yensen & Tarifa, 2003) até áreas antropizadas e bordas de florestas (Kasper et al, 2013).…”
Section: Agradecimentosunclassified